Effect of combined surgical and endovascular approach to lower limb venous ulcer - LI Tao, YANG Jing, YANG Hongwei, LIN Huan, WANG Zuhui, GUO Juanjuan, ZHU Guoxian (Waike lilun yu shijian, 2020)
Objective To investigate the clinical effect of combined surgical and endovascular approach in treatment of lower limb venous ulcer. Methods Patients with lower limb venous ulcer in the First Affiliated Hospital of Shenzhen University(Shenzhen Second People's Hospital) from January 2016 to December 2019 were retrospectively analyzed, and the clinical efficacy of combined surgical and endovascular approach was explored. Results A total of 127 patients with lower limb ulcer were enrolled including 22 cases with laser therapy for greater saphenous vein, 84 cases with stripping therapy and 30 cases (35 stents) with implantation of stent. The patients recovered using combined surgical and endovascular approach, and all but one patient discharged from hospital. One patient was without heal of ulcer. There was no ulcer recurrence shown by follow-up. Conclusions Treatment with combined surgical and endovascular approach could shorten the healing time of lower limb venous ulcer.